Data Literacy Intervention in Scientific Speaking Learning: Perspectives of Teachers and Students in High School - Faisal, Abdul Haris (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Data literacy interventions in learning are an important part of improving student competency. Data literacy is a form of new literacy development that is considered adaptive and mandatory for students to support the competencies they want to achieve, especially in scientific speaking. This study aims to investigate data literacy interventions in scientific speaking learning from the perspectives of teachers and students at the high school level. Data literacy skills are considered to have a positive impact on how students speak argumentatively. This study used descriptive qualitative methods and data collection techniques through interviews and questionnaires. Data analysis techniques through data collection, data presentation, data condensation, and conclusion drawing. The research findings indicate that teachers' perspectives on data literacy interventions have a good and positive impact on students' tendency to argue through scientific speaking activities, and learning activities with data literacy interventions stimulate students to be able to access, collect, sort, and analyze various data into information that can be communicated through scientific speaking skills. Student perspectives on data literacy interventions indicate that data literacy has a positive impact on supporting scientific speaking skills.